Beneficial Electrophysiological Effects of Rotigaptide Are Unable to Suppress Therapeutic Hypothermia-Provoked Ventricular Fibrillation in Failing Rabbit Hearts With Acute Ischemia–Reperfusion Injury - Lee, Hui-Ling; Chang, Po-Cheng; Wo, Hung-Ta; Liu, Hao-Tien; Wen, Ming-Shien; Chou, Chung-Chuan (Frontiers in Physiology, 2021)
Aims Whether therapeutic hypothermia (TH) is proarrhythmic in preexisting failing hearts with acute ischemia-reperfusion (IR) injury is unknown. Additionally, the effectiveness of rotigaptide on improving conduction slowing in hearts with IR injury is ambiguous. We investigated the electrophysiological effects of TH and rotigaptide in failing rabbit hearts with acute IR injury and determined the underlying molecular mechanisms. Methods and Results Heart failure was induced by right ventricular pacing (320 beats/min, 4 weeks). Rabbits with pacing-induced heart failure were randomly divided into TH (n=14) and non-TH (n=7) groups. The IR rabbit model was created by ligating the coronary artery for 60 min, followed by reperfusion for 15 min in vivo. Then, hearts were excised quickly and Langendorff-perfused for simultaneous voltage and intracellular Ca2+ (Cai) optical mapping. Electrophysiological studies were conducted, and vulnerability to ventricular fibrillation (VF) was evaluated using pacing protocols. TH (33 °C) was instituted after baseline studies, and electrophysiological studies were repeated. Rotigaptide (300 nM) was infused for 20 min and electrophysiological studies were repeated under TH. Cardiac tissues were sampled for Western blotting. TH increased dispersion and beat-to-beat variability of action potential duration (APD), aggravated conduction slowing, and prolonged Cai decay to facilitate spatially discordant alternans (SDA) and VF induction. Rotigaptide reduced dispersion and beat-to-beat variability of APD and improved slowed conduction to defer the onset of arrhythmogenic SDA by dynamic pacing and elevate the pacing threshold of VF during TH. However, the effect of rotigaptide on TH-enhanced VF inducibility was statistically insignificant. TH attenuated IR-induced dysregulation of protein expression, but its functional role remained uncertain. Conclusion TH is proarrhythmic in failing hearts with acute IR injury. Rotigaptide improves TH-induced APD dispersion and beat-to-beat variability and conduction disturbance to defer the onset of arrhythmogenic SDA and elevate the VF threshold by dynamic pacing, but these beneficial electrophysiological effects are unable to suppress TH-enhanced VF inducibility significantly.